(untitled) (Indonesian Art and Justice Review, 2025)
Art has the power to amplify the voices of marginalized communities, offering a platform for social justice and recognition. This paper explores how Indonesian artists and cultural organizations are working to elevate the voices of underrepresented groups, including ethnic minorities, women, LGBTQ+ communities, and indigenous peoples. By examining art exhibitions, community projects, and public performances, the study analyzes how marginalized communities use art to express their identities, tell their stories, and demand social and political justice. The paper also looks at the role of art in challenging stereotypes, addressing inequalities, and fostering solidarity across diverse groups in Indonesia, contributing to a more inclusive and just society.